2002
DOI: 10.1016/s0022-2836(02)01061-6
|View full text |Cite
|
Sign up to set email alerts
|

The Disulphide Mapping, Folding and Characterisation of Recombinant Ber e 1, an Allergenic Protein, and SFA8, Two Sulphur-rich 2S Plant Albumins

Abstract: We have cloned and expressed genes encoding the allergenic brazil nut 2 S albumin (Ber e 1) and the sunflower albumin 8 (SFA8) in the methylotrophic yeast Pichia pastoris. We show that both proteins were secreted at high levels and that the purified proteins were properly folded. We also showed that Ber e 1 is glycosylated during secretion and that the glycan does not interfere with the folding or immunoreactivity. The disulphide map of the Ber e 1 protein was experimentally established and is in agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
75
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 42 publications
(36 reference statements)
10
75
2
Order By: Relevance
“…The tertiary structure of the SFA8 in solution has been determined recently (24) and agrees with the tertiary structures of other members of the family and the model structure proposed for Ber e 1 (21). This conservation of the three-dimensional structure was exploited in the design of chimeric proteins for the mapping of the human structural IgE epitope of Ber e 1, whereby proteins containing exchanged domains were produced (25).…”
supporting
confidence: 70%
See 3 more Smart Citations
“…The tertiary structure of the SFA8 in solution has been determined recently (24) and agrees with the tertiary structures of other members of the family and the model structure proposed for Ber e 1 (21). This conservation of the three-dimensional structure was exploited in the design of chimeric proteins for the mapping of the human structural IgE epitope of Ber e 1, whereby proteins containing exchanged domains were produced (25).…”
supporting
confidence: 70%
“…The reverse-phase purified recombinant proteins were shown to be absent of endotoxin, as determined by an Endosafe Kit (Charles River Laboratories). Our previous results have unequivocally established that the recombinant proteins mimic their native counterparts in structural and biophysical properties (21)(22)(23). Recent nuclear magnetic resonance results (21) and disulfide mapping by mass spectra (21) have shown that the four intrachain disulfide bridges were properly established during the protein expression, folding, and secretion in the yeast expression system used.…”
Section: Brazil Nut and Sunflower 2s Seed Albuminsmentioning
confidence: 83%
See 2 more Smart Citations
“…CysV and CysVI are also highly conserved and flank a single residue whereas CysVII and CysVIII vary in their position and may be separated by 3-7 residues. Although (Rundqvist et al 2012) (a) (b) (Irwin et al 1990;Alcocer et al 2002;Pantoja-Uceda et al 2004a). The structures include a recombinant Brassica napus albumin (rproBnIb) that differs from the native BnIb protein by three residues (black) that join the small and large albumin subunit.…”
Section: Albumin Structurementioning
confidence: 99%